Hesitações em início de enunciados de crianças em aquisição de linguagem - Villega, Cristyane de Camargo Sampaio [UNESP] (2014)
Objective: (1) to verify the existence (or not) of hesitating marks in the beginning of utterances in children‟s discourse, (2) to characterize the hesitating marks found, and (3) to determine to what extent the presence / absence of hesitation marks in the beginning of the utterances could be explained by recoverable facts in children‟s discurses. METHODS: interview situations were analyzed with four children between 5-6 years old attending Child Level II in a public school of Childhood Education at the time of data collection. The interviews were recorded on audio and video, inside a soundproof cabin, with high fidelity equipment. Afterwards, the recordings were transcribed for six transcribers specially trained for this task. Transcription rules that prioritized detection points and hesitation marks were used. For the analysis of recoverable facts in the production conditions of children‟s speech, we adopted the dialog question-answer pair. RESULTS: We observed: higher incidence of utterances initiated without hesitating marks; no statistical difference between simple and combined hesitation marks; preference for silence (silent pause and rough cut) as hesitating mark used by children in early of its utterances, followed by sound (filled pauses and hesitated stretching) and support in grammatical structures (hesitated repetition and stuttering)); correlation between the presence / absence of hesitation in the beginning of utterance and question type (open/closed) carried out by the caller since, when the question was closed type, the utterances were initiated, preferably without hesitating marks, and when the question was open type, preferably with hesitated marks. CONCLUSION: Although children have started their utterances, preferably without hesitating marks, the presence/absence of these marks and the type of the hesitating marks showed to be dependent on the condition of children‟s discourse.